Reaction Mechanism of Formation of CaSO4 in AFBC - Ali, Ismat; Ali, M Mohsin (Bangladesh Journal of Scientific and Industrial Research, 2007)
Attempts have been made to investigate and predict the reaction mechanism of formation of calcium sulphate (CaSO4) in Atmospheric Fluidized Bed Combustor (AFBC). Formation of NOx, from nitrogen content to coal has been found beneficial for the oxidation of sulphur dioxide to sulphur trioxide. Bangladesh J. Sci. Ind. Res. 41(3-4), 167-170, 2006